Parallel worlds of faith and science in the Russian intellectual milieu - Petreshak, Nataliya (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
Book review: Teresa Obolevitch, Faith and Science in Russian Religious Thought, Oxford University Press, Oxford-New York 2019, pp.240.